"MISERY LOVES COMPANY": THE OTHER SIDE OF COVID-19 FOR SPOUSAL CAREGIVERS. (20th December 2022) - Geng, Jing; Calasanti, Toni; Giles, Sadie
Abstract: Gerontologists have voiced much concern about the potential for the pandemic to create social isolation risks for older people, especially older caregivers, for whom the lockdown cut off many sources of support. This presentation is based on a national study of older same-sex and heterosexual people who care for their spouses with Alzheimer's disease and related dementias. The qualitative, interview-based research began before the pandemic, and we were able to ask caregivers about their experiences during this public health crisis. Drawing on a total of 48 interviews, this presentation documents the surprising finding that, although caregivers discussed some challenges, they found much to say about the positive aspects of the lockdown and continued restrictions, including not having to rush for appointments or social engagements and being less frustrated with their care receivers as a result. They also described instances of greater social connection rather than less through the use of technology. In addition, some caregivers found that being with their care receiver all day gave them greater insights into disease progression and how to manage it, as well as greater intimacy. Finally, the phrase "misery loves company" was used to convey that the pandemic provided a situation wherein other people also were restricted in ways that some caregivers had been prior to the pandemic; as a result they felt others had more of an appreciation of what their lives had been like.